Buying and Selling Gold in Cashless Perspective of Sharia: DSN-MUI Fatwa Study No. 77 Year 2010 - Muhammad Faqih Abdillah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2022)
DSN-MUI Fatwa No. 77/DSN-MUI/V/2010 concerning buying and selling gold in cash which was issued on June 3 2010, DSN-MUI states that buying and selling in cash is permissible (mubah), as long as gold does not become the official medium of exchange (money), either through ordinary buying and selling or buying and selling murabaha. It is interesting to study the reason for this fatwa being issued and the suitability of the legal advice of the DSN-MUI with the legal advice of the MUI in issuing this fatwa. This research is a type of library research using a descriptive analysis approach. In this study it can be concluded that: the reasons for the permissibility of buying and selling gold in cashless manner in the DSN-MUI fatwa No. 77/DSN-MUI/V/2010, DSN-MUI interprets the Hadith of the Prophet SAW regarding buying and selling gold in a contemporary (contextual) way. This can be seen from the opinion of the DSN-MUI which states that gold and silver are goods (sil'ah) that are sold and bought like ordinary goods, and no longer saman (price, money). So that the result of the DSN-MUI's legal advice on buying and selling gold in cash is considered permissible (mubah).